IN THE MATTER OF: STATE OF MINNESOTA V. PHILLIP MORRIS, ET AL DAVID M. HORAZDOVSKY, TI 30.02(F) VOL. 1, OCTOBER 16, 1997 - HORAZDOVSKY, DAVID; STIREWALT & ASSOCIATES (Tufts Archival Research Center, 2007)
Testimony given by David M. Horazdovsky during the trial of the state of Minnesota vs. Philip Morris. Discusses the Tobacco Institute's fiscal contributions to Political Action Committees and Horazdovsky’s lobbying activities. Includes index of keywords spoken during the deposition.